Enhancing Teacher-Student Collaboration through Digital Technologies - Usmonov Umid Farxodovich (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: The integration of digital technologies in education provides new opportunities to strengthen collaboration between teachers and students. By using interactive platforms, communication tools, and digital learning resources, educators can create environments that promote active participation, real-time feedback, and joint problem-solving. This study explores methodological approaches for enhancing teacher-student collaboration through digital technologies, emphasizing pedagogical strategies, practical applications, and benefits for learning outcomes. Drawing upon existing research and contemporary studies, the paper highlights how digital tools can facilitate personalized learning, improve engagement, and foster a collaborative classroom culture.